Religion and Public Life in the Mountain West: Sacred Landscapes in Transition - Silk, Mark; Shipps, Jan (Rowman & Littlefield Publishers, 2004)
Huge mountain ranges and vast uninhabited areas characterize the Mountain West. The region is home to several dense urban centers, but there is enough space between cities for three very distinct religious cultures to develop. Arizona and New Mexico's religious public life is still dominated by the Catholic church which was in place three centuries before these areas became U.S. states. Mormons came to Utah and Idaho in the 19th century to set up their own church-state and only later were admitted to the Union. Religious minorities from Native Americans to 'mainstream' Protestants must contend with these religious establishments. In the third subregion of Colorado, Wyoming, and Montana no one religious body dominates and many inhabitants claim no religious affiliation at all. Religion and Public Life in the Mountain West explores these three distinct religious regions but then goes on to see how they work together and what they have in common.